High-performance computing platforms: current status and development trends - Antonov, A.S.; Afanasyev, I.V.; Voevodin, Vl.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2021)
This paper provides an overview of the current state of supercomputer technology. The review is done from different points of view — from the construction features of modern computing devices to the features of the architecture of large supercomputer complexes. This review includes descriptions of the most powerful supercomputers in the world and Russia since the early of 2021 as well as some less powerful systems that are interesting from other points of view. It also focuses on the development trends of the supercomputer industry and describes the most famous projects for building future exascale supercomputers.